Complexation of neurotransmitters ‒ dopamine, serotonin and melatonin ‒ with a DTPA-based cyclophane of high rigidity: 1H NMR shift and line-broadening. Issue 9 (2nd September 2017) - Arvízu-Santamaría, Ana Gabriela; Navarro, Rosa Elena; Soberanes, Yedith; Velázquez, Enrique F.; Santacruz, Hisila; Inoue, Motomichi
Abstract: The 1 H NMR signals of the titled neurotransmitters undergo up-field shift accompanied by line-broadening in NMR titration with the DTPA-based cyclophane at pD 7.3; the cyclophane consists of a 4, 4′-bis(1, 1′-biphenyl-4, 4′-dihydroxy)dianiline unit cyclised by a DTPA (diethylenetriaminepentaacetate) group through two amide linkages. Changes in chemical shifts of dopamine indicate the formation of a 1:1 complex with the formation constant K 1 400 M −1 ; the complex of serotonin is likely to form a 2:1 host‒guest complex with β 2 ≈ 10 5 M −2 ; melatonin does not form a complex with definite stoichiometry. The primary binding forces in the dopamine and serotonin complexes are electrostatic interaction between cationic neurotransmitter and anionic cyclophane molecules, and the resulting ionic pairs are stabilised by encapsulation. The electrostatic interaction is weakened by electrolytes; in 0.1 M Trizma buffer, dopamine does not yield a definite complex, and serotonin forms a 1:1 complex with K 1 80 M −1 . Extreme line-broadening of neurotransmitter signals suggests that the molecular motion of the guest molecule is slowed in the complex by interactions with the receptor molecule whose internal molecular motion is quenched partially. The high rigidity of the cyclophane enhances intermolecular interaction in the hydrophobic regions to prolong the lifetime of the complex. Abstract :